Effectiveness of I-Learn among Art & Design student majouring in graphic design In UiTM Melaka City Campus / Ahmad Amaluddin Mohd Azman - Mohd Azman, Ahmad Amaluddin (2014)
When you talk about learning online, most people think about distance learning programs, where students can take classes to get a degree from home. But online classes are becoming a part of life on campus at a growing number of collages across the country (WPRI, 2010). Students nowadays are no stranger towards technologies like the major online social networking site called Facebook, Twitter, Instagram and etc. In these modem era, having all the gadget is a normal thing and it is a necessity to some people as it works as their main tool for communicating with one another. However, in education there have been a revolution where universities and institution have come out with method to give attraction in learning process by introducing e-lerning. By having this in learning environment, it can give benefit to both teacher and also students. Yet, students in the art department majoring in graphic design shows less interest in using the I-Learn system that works as an e-lerning material provided by the University. There are many social networking site on today's World Wide Web and is been used by students but not when it comes to logging onto the I-Learn system. Through this, new approach has been founded which is combining the existing I-Learn with social media platform that would attract student attention. There are big chance that students will use the I-Learn more frequently when they can still have the social network experience.